Smart Infrastructure Evolution: Understanding the Societal Implications of Real-Time Systems - Mayur Bhandari (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of distributed real-time systems on smart cities and public infrastructure, highlighting their profound influence on societal development and urban living. Through an analysis of current implementations and emerging technologies, this article explores how these systems are revolutionizing various sectors, from traffic management and public safety to education and creative industries. It demonstrates that while distributed real-time systems offer significant advantages in urban efficiency, sustainability, and quality of life, they also present complex challenges regarding privacy, digital equity, and ethical governance. By investigating real-world applications and their outcomes, this article provides insights into the delicate balance between technological advancement and societal well-being. Drawing from established frameworks and recent developments in cloud computing and IoT integration, it presents a comprehensive evaluation of both the opportunities and challenges inherent in smart city implementations. This suggests that successful integration of distributed real-time systems requires careful consideration of technological capabilities, social implications, and ethical guidelines, ultimately contributing to the broader discourse on sustainable urban development and digital transformation.